PENGARUH E-MONEY DAN PENETAPAN HARGA TERHADAP KUALITAS PELAYANAN SERTA DAMPAKNYA TERHADAP KEPUASAN PENUMPANG TRANSJAKARTA (STUDI KASUS PENUMPANG TRANSJAKARTA DI KORIDOR VIII JURUSAN LEBAK BULUS-HARMONI) - Cicih Ratnasih dan Randhy Toar Kadang (Fakultas Ekonomi Universitas Borobudur, 2016)
This study aims to determine whether there is a relationship between E-Money and Pricing on Service Quality and its impact on Passenger Satisfaction TransJakarta. Populasidalam this research is TransJakarta Passenger especially Students who have e-money card and are in Corridor VIII TransJakarta.Variabel independent in this research is E-Money, Pricing and Quality of Service where independent variable is Passenger Satisfaction. For a collection method datadilakukan by using a questioner. The data collected is analyzed by analyzing descriptive and statistical analyzes using SPSS version 22, whereas the underlying jihipotesis is Path Analysis.Based on the results of the study, it can be concluded that there is a positive and significant influence on E-Money and the Pricing of Service Quality directly, there is a positive and significant influence on E-Money and Pricing on Passenger Satisfaction directly, and there is a positive and significant influence between E- Passenger Satisfaction through Quality of Service indirectly. And there is a positive and significant influence between Price Determination of Satisfaction Penumpng through Service Quality indirectly. Keywords : Determination of Price, Quality Of Service, Passenger Satisfaction